2006
DOI: 10.1007/s10464-006-9056-1
|View full text |Cite
|
Sign up to set email alerts
|

Realities and Myths of Safety Issues for Community Researchers Working in a Marginalized African American Community

Abstract: Community psychologists often conduct research in collaboration with marginalized communities in which safety is an issue. However, we rarely talk about what specific safety issues we experience and how we deal with them. Our story describes the realities and myths of neighborhood safety that were experienced in a low-income African American neighborhood of Chicago, while collaborating on a project designed to increase access to the Internet to obtain health information. We examine both the challenges experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This trend toward more critical social sciences has given rise to a number of partnership approaches to research and practice (Bok 1982;Boyer 1990;Israel et al 1998). Studies show that solid partnerships with communities are vital sources for teaching, research and practice (Johnson Butterfield and Soska 2005;Suarez-Balcazar and Kinney 2006). The process of collaboration is interactive and based on common goals; and it allows for the generation of different solutions to problems and concerns (Silka 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This trend toward more critical social sciences has given rise to a number of partnership approaches to research and practice (Bok 1982;Boyer 1990;Israel et al 1998). Studies show that solid partnerships with communities are vital sources for teaching, research and practice (Johnson Butterfield and Soska 2005;Suarez-Balcazar and Kinney 2006). The process of collaboration is interactive and based on common goals; and it allows for the generation of different solutions to problems and concerns (Silka 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Collaborative Problem-Solving (CPS) Model is a community-based approach that stakeholders can use to achieve long-term solutions to local environmental health issues or concerns [ 8 , 10 , 11 ]. The methodology can be applied to situations that entail collaboration, and can be most useful when dealing with environmental justice issues that are complicated, involve many stakeholders, and where conflicts need to be resolved [ 14 , 15 , 16 , 17 ]. Since its introduction, the CPS Model has been used successfully in many situations around the country.…”
Section: Introductionmentioning
confidence: 99%
“…Community-campus partnerships such as the CAPs partnership can help address issues of concern to the community including environmental injustice and environmental health disparities while providing opportunities for academics to perform applied transdisciplinary research. Research has shown that a strong partnership with communities is a valuable source for teaching, research and practice [ 14 , 15 ]. This interactive process of collaboration is based on common goals that lead to the development of different solutions to community-level problems and concerns.…”
Section: Introductionmentioning
confidence: 99%
“…One set of stories looks at issues that arise in the context of small group interventions to increase individual awareness and sensitivity to diversity (Ceballo, Ramirez, & Maltese, 2006;Chronister, 2006;Vasquez, 2006). A second set of stories tells of issues that emerged when working to address intergroup relations-some doing so within a particular setting, like a school, community-based organization, or religious institution (Borg, 2006;D'Augelli, 2006;Levine, 2006;Martorell & Martorell, 2006;Shpungin & Lyubansky, 2006;Suyemoto & Fox Tree, 2006); and others doing so within a broader community (Berryhill & Linney, 2006;Daniels, 2006;Langhout, 2006;Lee & Calvin, 2006;Messinger, 2006;Ross, 2006;Suarez-Balcazar & Kinney, 2006). A final set of stories deals with diversity issues that emerged in the context of forming research partnerships, whether it be to better understand an understudied community (Brodsky & Faryal, 2006;Gone, 2006;Miller, Forte, Wilson, & Greene, 2006;Paxton, Guentzel & Trombacco, 2006) or to develop and/or assess programs within ethnic/minority communities (Coppens, Page & Thou, 2006;Small, Tiwari, & Huser, 2006).…”
mentioning
confidence: 99%